Analisis Peran Implementasi Manajemen Mutu dan Kepemimpinan Transformasional terhadap Performa Pendidik: Analysis of the Role of Implementation of Quality Management and Transformational Leadership on Educator Performance - Evi Gusliana; Akhmad Ramli; Enny Diah Astuti; Faisal Abubakar; Bayu Purbha Sakti; Lazuardy Alief (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Human resources' capacity and competence greatly determine a nation's competitiveness and ability to compete. The performance of its human resources greatly influences organizational performance. The competitiveness of a country is greatly influenced by the quality and performance of its population. Realizing the importance of the quality of human resources, educational institutions, especially schools and teachers, have a crucial role in preparing students as assets and future successors of the nation. This study uses a qualitative methodology, including interviews, observations, literature analysis, and previous research. The main focus of this study is to investigate educators or teachers in Indonesian schools with similar variables and objects. The unit of analysis in this study involved teachers working in five major cities in Indonesia, while the observation unit included principals, students, and parents of students. A correlation exists between implementing quality management, transformational leadership style and educator performance. Based on the results of interviews, observations, studies of literature and previous studies, implementing quality management that runs well and a transformational leadership style positively affects teacher performance. Suppose schools can design a quality management system and implement a good quality assurance process, where the quality assurance process focuses on administrative and quality processes in academic activities such as learning and teaching. In that case, it will certainly have an impact on teacher performance.